56th U.S. Rock Mechanics/Geomechanics Symposium 2022
DOI: 10.56952/arma-2022-0306
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Proppant Placement Efficiency at the Intersection of Induced and Natural Fractures

Abstract: The intersection of the pre-existing natural fractures (NF) with the hydraulic fractures (HF) forms a complex fracture network, which allows for increased well productivity. However, the complex fracture geometry may adversely affect the proppant placement and its transportation inside the fractures. The study reports the results of the Lattice numerical simulations of proppant placement at the intersection of fractures. Sensitivity analysis was performed to investigate the effect of pre-existing fracture fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Horizontal drilling and hydraulic fracturing have significantly improved unconventional reservoir recovery as studied by Merzoug et al [40]. Although this combination has been successful in providing access to previously inaccessible resources such as shale formations [41], they still suffer from some challenges.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Horizontal drilling and hydraulic fracturing have significantly improved unconventional reservoir recovery as studied by Merzoug et al [40]. Although this combination has been successful in providing access to previously inaccessible resources such as shale formations [41], they still suffer from some challenges.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…They believed that the interproppant and proppant wall interactions become dominant, which adds turbulence to the flow [8]. Merzoug et al, 2022 discussed proppant placement efficiency considering the hydraulic fracture and natural fracture interaction. They revealed that the effect of the pre-existing fracture friction angle and the angle of approach, as well as the differential horizontal stress on hydraulic fracture and natural fracture interaction mechanisms and proppant transport and placement [9].…”
Section: Introductionmentioning
confidence: 99%
“…Merzoug et al, 2022 discussed proppant placement efficiency considering the hydraulic fracture and natural fracture interaction. They revealed that the effect of the pre-existing fracture friction angle and the angle of approach, as well as the differential horizontal stress on hydraulic fracture and natural fracture interaction mechanisms and proppant transport and placement [9]. Zheng et al, 2023 introduced a CFD (Computational Fluid Dynamics) -DEM (Discrete Element Method) technique to investigate the effects of different roughness characterization parameters on the efficiency of proppant transport using supercritical CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This approach aligns with the industry's goal to remain a leading energy system while addressing environmental concerns. By effectively managing and utilizing CO 2 emissions for oil recovery, the industry not only enhances its resource efficiency but also makes significant strides toward sustainability [7].…”
Section: Introductionmentioning
confidence: 99%